1997
DOI: 10.1590/s0004-282x1997000500003
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and quantitative study of the myenteric plexus of the ascending colon of rats subjected to proteic desnutrition

Abstract: We carried out this study with the purpose of contributing on the effects of the proteic desnutrition on the morphological aspects and quantitative analysis of the neurons in the myenteric plexus of the ascending colon of adult Rattus norvegicus. Twenty adult rats were divided into two groups: in one of them, we offered a normal ration with proteic level of 22% (control group) and in the other, a ration with a proteic level of 8% (experiment group) during 120 days. We did the whole-mount preparations for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
47
1
12

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 13 publications
12
47
1
12
Order By: Relevance
“…The importance of proteins in the processes of synthesis of substances for growth and tissue re-newal was demonstrated by the lower weight gain and smaller bowels of the experimental animals, similar to the findings in rats with protein desnutrition 16 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The importance of proteins in the processes of synthesis of substances for growth and tissue re-newal was demonstrated by the lower weight gain and smaller bowels of the experimental animals, similar to the findings in rats with protein desnutrition 16 .…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, about 50.5% of the nitrergic neurons and 27.2% of the NADH-diaphorase positive neurons of the ascending colon were not evidenced. Significant reductions in the number of myenteric neurons of malnourished rats were also verified in other investigations, and have been attributed to the nutritional deficiency to which the animals were subjected [8][9][10][11]16 .…”
Section: Discussionmentioning
confidence: 55%
“…The measurement of the yeast cell sizes was carried out with the aid of an Olympus CBB microscope coupled with a micrometer disc. We measured the major transverse and longitudinal axes of 100 viable cells of each preparation 19 .…”
Section: In Vitro Evaluation Of Fungal Strains Morphometrical Charactmentioning
confidence: 99%
“…Myenteric neurons were considered large when the areas of cell body profiles were above the mean+SD, small when the areas were below the mean-SD and medium when the areas were on the interval of the mean±SD. This procedure of classification was the same as that employed in other morphometric analyses previously carried out in our laboratory 5,6,8 .…”
Section: Discussionmentioning
confidence: 99%
“…The morphoquantitative studies of the myenteric plexus carried out until the 80s used to consider a given segment of the digestive tube, but recently it was found that different regions of the stomach and of the intestinal circumference also differ in their features and in their sensitivity to experimental procedures [4][5][6] . This fact deserves attention because phylogenetic, age-related and pathophysiological comparisons can be interpreted erroneously due to the random selection of neurons around the intestinal circumference.…”
mentioning
confidence: 99%